Subcutaneous Alemtuzumab as Salvage Therapy for Acute Kidney Transplant Rejection Following Thymoglobulin Anaphylaxis: A Pediatric Case Report - Kevin W. O'Connor; Serena Bagnasco; Cozumel Pruette; Elizabeth Goswami; Olga Charnaya (Pediatric Transplantation, 2026)
ABSTRACT Background Acute kidney allograft rejection is a significant cause of graft dysfunction in pediatric transplant recipients. Standard of care for moderate to severe acute T‐cell‐mediated rejection among pediatric transplant recipients includes lymphocyte‐depleting agents such as rabbit anti‐thymocyte globulin (rATG). However, intolerance to or contraindications to rATG may limit its use and necessitate alternative immunosuppressive strategies. Alemtuzumab, a humanized monoclonal antibody targeting CD52, induces profound depletion of T‐ and B‐ lymphocytes and has been used in the transplantation setting. However, data remain limited for pediatric rejection, and the precise role for alemtuzumab is not well defined. Case Presentation We report a 12‐year‐old male with end‐stage kidney disease secondary to congenital renal dysplasia who underwent deceased donor kidney transplantation and presented 9 years post‐transplant with acute allograft dysfunction. Evaluation revealed a rise in serum creatinine, subtherapeutic tacrolimus levels, and increased donor‐specific antibodies. Kidney biopsy demonstrated Banff grade IIA T‐cell‐mediated rejection with features of antibody‐mediated rejection. Initial treatment included high‐dose corticosteroids and intravenous immunoglobulin. rATG therapy was initiated but discontinued due to anaphylaxis. The patient subsequently received a 30‐mg dose of subcutaneous alemtuzumab, which was well tolerated. B‐ and T‐lymphocyte populations were suppressed on flow cytometry analysis. Kidney function significantly improved, repeat biopsy showed marked improvement in tubulointerstitial inflammation, and graft function remained stable at follow‐up. Conclusions This case highlights the potential role of alemtuzumab as an alternative lymphocyte‐depleting therapy for the treatment of acute rejection in pediatric kidney transplant recipients, particularly when rATG is contraindicated. Moreover, treatment with alemtuzumab may preclude the need for additional B‐cell directed therapy in cases of mixed T‐cell‐ and antibody‐mediated rejection. Further studies are needed to better define its safety, efficacy, and optimal role in this population.